Dissecting the role of gut microbiota heterogeneity in the onset of chronic lung diseases - Ya Lin; Xiaoxiao Zhang; Ziyi Zuo; Yijia Xiao (AMB Express)
Abstract Evidence from observational studies and clinical trials has reported that gut microbiota (GM) was associated with chronic lung diseases (CLDs). However, the causal relationships between GM and CLDs have yet to be fully ascertained. The Mendelian randomization (MR) based causal analysis was performed using the genome-wide association study (GWAS) summary statistics from the MiBioGen and FinnGen consortium. GM served as exposure, and CLDs were taken for outcomes. Inverse variance weighted, MR-Egger, and weighted median methods were utilized to examine the causal association between GM and CLDs. The sensitivity analyses were then conducted to validate the robustness of the results. Further, the reverse MR analysis was performed to evaluate the possibility of reverse causation. Finally, the in-silico in-situ microbiota resequencing (ISSMR) of high-throughput sequencing data was utilized as a supplement to dissect the role of microbiota spatial distribution disturbance on the onset of idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD). This study revealed that GM had causal associations with CLDs. Conversely, reverse MR analysis suggested that the presence of COPD and IPF may causally influence the abundance of specific GM. And ISSMR further provided clues to the interaction of intra-tissue as well as gut microbe disturbance in IPF and COPD from synergistic or independent perspectives. In short, the MR analysis revealed a causal relationship between GM and CLDs from a host genetic perspective, and ISSMR extended the host-microbe regulatory modality from a microbe genetic perspective, thus together providing novel insights into the gut microbiota-mediated development mechanism of CLDs.